A study of reproductive health problems among rural adolescent girls of Mohanpur block of West Tripura district - Subrata Baidya; Manjulika Debnath; Rituparna Das (Al Ameen Medical College, 2014)
Objectives: (1) To study the various reproductive health problems among rural adolescent girls in study area. (2) To ascertain the knowledge of reproductive health and health care-seeking behavior among rural adolescent girls. Background: Adolescence is characterized by menarche among girls which is often associated with several reproductive problems. It is necessary to assess the enormity of the problem to take appropriate interventions. Materials and Method: This cross-sectional study was conducted in July and August, 2011 in a randomly selected sub-center area, under Mohanpur CHC. The sample size was calculated and 200 adolescent girls in the age group 10-19 years were selected by simple random sampling for the study. Results: The study showed that the prevalence of dysmenorrhea was 59.50 percent. 14.50 percent of the respondents had menstrual irregularity, 5.50 percent had menorrhagia, while Pre-Menstrual Syndrome was perceived by 8.50 percent of the respondents. Higher age of attainment of menarche had significant trend of pain during menstruation. 37.00 percent of the respondent adolescent girls used household remedy for reproductive health problems. Conclusions: The study indicates that the problem is enormous and there is need for appropriate intervention to utilize and upgrade the services for the benefit of the adolescent girls.